2010
DOI: 10.1177/0883911509354230
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of Melittin: Structural Characterization and Hemostatic Effects

Abstract: To promote and understand the structure-property relationship for hemostasis, we modified melittin (MLT) using a four-arm poly(ethylene glycol) (PEG) with N-hydroxysuccinimide ester. The PEGylation was characterized by FTIR, MALDI-MS, NMR, a bicinchoninic acid assay, circular dichroism, hemolysis assay, and thromboelastography. Changes in the reaction conditions affected the extent of the modification, the numbers of MLT conjugated to PEG arms, and possible PEGylation sites. The reaction at pH 9.2 with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
(94 reference statements)
0
11
0
Order By: Relevance
“…Mel showed characteristic absorption peaks at 1657 and 1539 cm −1 , corresponding to the stretching of the C=O and N-H bonds of the amide group, respectively. 46 Mel-loaded NISVs showed absorption signals at wavelengths of 1651 and 1555 cm −1 , which were slightly shifted from the characteristic signals of Mel. This presumably was due to the interaction between the amide groups of Mel and the NISVs.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 90%
“…Mel showed characteristic absorption peaks at 1657 and 1539 cm −1 , corresponding to the stretching of the C=O and N-H bonds of the amide group, respectively. 46 Mel-loaded NISVs showed absorption signals at wavelengths of 1651 and 1555 cm −1 , which were slightly shifted from the characteristic signals of Mel. This presumably was due to the interaction between the amide groups of Mel and the NISVs.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 90%
“…Previous reports have shown that it is possible to (at least approximately) determine the composition of PEGylated protein systems using spectrometric techniques such as matrix‐assisted laser desorption ionization time‐of‐flight (MALDI‐TOF) mass spectrometry . In the following, the calculated and experimental distributions of PEG ligands are compared for a number of protein systems with systematically varying N 0 to evaluate the applicability of Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Various strategies have been explored to overcome the aforementioned problems, including the alteration of melittin sequence to reduce its hemolysis, PEGylation or glycosylation to increase the stability and prolong the in vivo biological half-life, or the conjugation of targeting molecules, such as the antibody, to increase cancer cell specificity. However, these methods may decrease the membrane-lytic activity of melittin in cancer cells and have no considerable effect on reducing melittin’s hemolytic activity and tissue toxicity.…”
Section: Introductionmentioning
confidence: 99%